PERAN ORANG TUA DALAM PEMBELAJARAN BLEANDID LEARNING DI TK DHARMA WANITA PERSATUAN 1 TERGALGONDO - Lutfiah Indriani; Eko Setiawan; Ari Kusuma Sulyandari (UNISMA, 2022)
This study describes the role of parents in the implementation of blended learning learning during the covid-19 pandemic at Dharma Wanita Persatuan 1 Tegalgondo, Tegalgondo. The methodology in this study was a qualitative study of parents and 3-year-olds. Informants under the age of 6, techniques for collecting data through observations, interviews and documents. The results suggest that involving parents in implementing blended learning during a pandemic can act as a facilitator, motivator, teacher, and influencer. In addition, the difficulties faced by parents include: electronic facilities, internet and limited time.